LEAD EROSION IN PERMANENT PACEMAKER: A CUMBERSOME COMPLICATION - Shah, Bakhtawar; Awan, Zahid Aslam; ullah, Tahmeed; Khan, Zahoor Ahmed (Journal of Ayub Medical College Abbottabad, 2014)
Background: Lead erosion is one of the troublesome complications which are very difficult to treat and most of the time leads to device explanation and replacement prematurely. Methods: From 2005 to 2011, total 415 pacemakers were implanted in our cardiology department at Hayatabad Medical Complex Peshawar. The patients were followed regularly at six month interval or more frequently in case there were complications. At every visit we inspected the wound site, electrocardiography was done and device was analyzed with compatible programmer for the device. If there was soreness at the site of implantation, patient was seen more frequently and if there was erosion of skin, wound was re-opened margin refreshed and wound closed. Initially we closed the wound in two layers after reopening but we got repeated erosion with this method and so we buried the leads sub-muscularly as change strategy which again proved unsuccessful. Results: During the six years study about 415 permanent pacemakers were implanted. During this time period, we received: three lead erosion, which were re-positioned. There were recurrence in two cases and they were again subjected to procedure with a change strategy; by burying the leads in muscles, which proved unsuccessful. Conclusion: Leads erosion can be prevented by carefully burying leads in three layers first in muscle followed by subcutaneous tissue and then closing the wound by suturing the skin during initial implantation. Keywords: Permanent Pacemaker, lead erosion, implantable cardioverter-defibrillator, electrocardiography, atrio-ventricular node